Adaptación y madurez precoz de maíces híbridos tropicales introducidos en la E.E. El Porvenir - San Martin - Tello Salas, Cheryl (2003)
The present work of investigaci6n was carried out in the area of ​​the Experimental Station "El Porvenir" in the Valle del Bajo Mayo, province of San Martin, geographically characterized by having the following coordinates: West Longitude 76 ° 5 ', 6 ° 35 'south latitude and 356 meters above sea level; Aiming to evaluate v Adaptation of Tropical hybrid corns and maturity Precocious PERFORMANCE IS FUNCTION AND PERFORM Economic Analysis of the best treatments. Performance and Complementary vegetative characteristics were evaluated using statistical design randomized complete block (RCBD) with 3 replications and 20 treatments, the results Were analyzed using analysis of variance and multiple significance test of Duncan. The experimental soil was residual source flat surface with clayey, alkaline reaction (pH = 7.8), organic matter content media (3.1%), nitrogen and phosphorus total content of potassium and high. The planting distance was 0.80 m. Between rows and 0.50 m. Between blows, with a plant density of 50,000 plants / ha. Composting is made using the dose of 120-80-60 kg of NPK / ha, applied to 50% of nitrogen, phosphorus together with one despu6s days of sowing and the remaining 50% Nitrogen 10 to 40 days after planting and Receiving a total rainfall of during the growing season of 409.6 mm and average temperature of 27.1 ° C. The results obtained according to the statistical analysis, it is concluded that there was: Significant differences between treatments in grain yield in 14% of humidity, whose yields ranged from 6,966 to 4,676 kg / ha which corresponded to the Hybrid CMS 981,016 and CMS 991 016, e! Major and minor respectively. Mandated: agronomic characteristics evaluated and retell benefit / cost m, it was identified a Hybrids CMS 981016 and CMS 991002, As promising good potential for cost performance and economically, with values ​​Net exceeding thousand nuevos soles per hectare Production profitability with the mayor to 47%.